New Florida Foliage Plant Cultivar: 'Red Hot' Anthurium - Richard J. Henny; Jianjun Chen; Terri A. Mellich (EDIS)
ENH-1099, a 4-page illustrated fact sheet by R.J. Henny, J. Chen, and T.A. Mellich, describes this cultivar of anthurium developed as a flowering potted foliage plant, its performance and availability. Includes references. Published by the UF Department of Environmental Horticulture, April 2008.